Digital Transformation and Leadership: The Mediating Role of Organizational Adaptation in Performance - Permana, Tatiek Ekawati; Chaerudin, Ruli Mochammad; Sonjaya, Yana; Rustiadi, Rizzky (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study examines the influence of digital transformation and digital leadership on employee performance through organizational adaptation in private universities. By situating informatization, HRM systems, and leadership styles within adaptive processes, the research provides empirical evidence of how digital integration fosters workforce performance. A quantitative approach was employed with 352 respondents, including HR staff, lecturers, and administrators from a private university in Bandung using a digital HRM system. Data were gathered via structured questionnaires and analyzed using SEM-PLS with SmartPLS 4.0. Results show that digital transformation and leadership exert both direct and indirect effects on performance through organizational adaptation. The academic contribution lies in extending HRM and leadership literature by framing digital leadership as a mechanism that converts digital transformation into sustainable performance via adaptation. Practically, the findings underscore the need to strengthen adaptive capacity, enhance digital competencies, and cultivate digital leadership in higher education institutions.